Penerapan Model Pembelajaran Problem Based Learning (PBL) disertai Media Google Earth untuk Meningkatkan Kemampuan Literasi Geografi Peserta Didik di SMA Negeri 1 Kartasura - Lintang Ayu Mustika Kencana; Sugiyanto Sugiyanto; Singgih Prihadi (Universitas Sebelas Maret (UNS), 2025)
This study was conducted to examine the differences in students' geographic literacy abilities and to assess the effectiveness of the application of the Problem Based Learning learning model combined with Google Earth media on geographic literacy in the Geography subject Phase E of class X of SMA Negeri 1 Kartasura in the 2024/2025 Academic Year. The study used a quasi-experimental method with a cluster random sampling technique. Data were collected through tests, observations, and documentation. The results showed that the use of the Problem Based Learning model assisted by Google Earth was able to improve students' geographic literacy abilities. Based on data analysis, the posttest score in the experimental class was higher than the class using the Student Teams Achievement Divisions model, with an average of 81.57 in the experimental class and 73.05 in the control class. Statistical tests showed a t-value of -6.092 with a significance of 0.000, and an N-Gain value of 0.44 in the control class and 0.62 in the experimental class. Thus, the results of the study confirmed that the Problem Based Learning model supported by Google Earth media was effective in improving students' geographic literacy.